Analysis of Student Learning Problems in Entomology Lectures - Hartono, Adi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2025)
This research aims to analyze various problems and difficulties of students in studying Entomology. The research was conducted using a survey method. The data collection technique uses a questionnaire containing 20 validated questions regarding aspects of students' learning difficulties in studying Entomology. The research data were analyzed descriptively using the Miles and Huberman approach which consists of three steps, namely: data reduction, data display, and data conclusion. The results of the research show that the dominant factor that causes problems for students in studying Entomology is material that they feel is confusing due to the many terms that must be mastered, the learning mechanism is not interactive, and the minimal use of media and reference sources that are interesting and relevant to the topic of the material being studied. Thus, it can be concluded that students' problems in taking Entomology courses lie in three main aspects, namely material, learning mechanisms, and references that are relevant to the topic being studied.